Identification of β-carotene and β-sitosterol in methanolic extract of Dipteracanthus patulus (Jacq) nees and their role in antimicrobial and antioxidant activity - Shrinivas B Bumrela; Suresh R Naik (International Journal of Phytomedicine, 2011)
The Dipteracanthus patulus (Jacq) nees is undershrub belonging to the family acantheaceae. Antimicrobial activity (disc diffusion method) and antioxidant activity by different in-vitro methods (DPPH, hydrogen peroxide, nitric oxide radical scavenging and reducing power) of methanolic extract of Dipteracanthus patulus (MEDP) was evaluated. The qualitative and quantitative estimation of β-carotene and β- sitosterol in MEDP was carried out by high performance thin layer chromatography (HPTLC). The total phenolic content of was determined by Folin-Ciocalteu method. Experimental findings indicate promising antimicrobial activity (antibacterial and antifungal) and potent antioxidant activity of MEDP. In addition, phytochemical analysis and spectral studies of MEDP were also performed. It is presumed that antimicrobial and antioxidant activity observed with MEDP may largely be attributed to the presence of major phytoconstituents (β-carotene, β-sitosterol and iridoid glycosides) and other minor components may participate as promoters.